Massive Open Online Courses (MOOC) dalam Proses Digitalisasi Pembelajaran di Perguruan Tinggi - Handyka Oktra Rajagukguk; Rugaiyah; Linda Ika Mayasari (Didaktika: Jurnal Kependidikan, 2025)
This study aims to describe how Massive Open Online Courses (MOOCs) support the digitalization of learning in higher education, with a focus on their contribution to improving the quality of higher education. Using a qualitative method based on literature studies, this study analyzes various academic sources and MOOC implementation practices at the global and national levels. The results show that MOOCs have great potential in expanding access to education, providing learning flexibility, and supporting the development of essential skills, such as digital literacy and cross-cultural collaboration. In addition, MOOCs contribute to increasing the competitiveness of higher education through global collaboration and diversification of learning methods. However, challenges such as uneven infrastructure and low participation rates require a strategic approach, such as the integration of hybrid learning and innovation in course design. With optimized implementation, MOOCs can be a major catalyst in building inclusive, adaptive, and globally competitive higher education.